2013
DOI: 10.4012/dmj.2013-077
|View full text |Cite
|
Sign up to set email alerts
|

Wear of metal-free resin composite crowns after three years in service

Abstract: To compare differences between the wear behavior of two types of metal-free resin composite crown with a control after three years in clinical service. Sixty-six participants needing one to three posterior single crowns were fitted with 120 crowns. Abutment teeth were randomly assigned to three groups: 40 resin composite crowns with fiber-reinforced framework, 40 resin composite crowns without fiber-reinforced framework, and 40 metal-ceramic crowns. To assess wear, gypsum replicas of the crowns were fabricated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
0
6
1
1
Order By: Relevance
“…The wear rates differed significantly between different research groups; Etman et al [38] stated wear of 148 μm after first year for lithium disilicate glass-ceramic posterior crowns, whereas Kramer et al [39] determined it as 78 μm after 4 year for ceramic inlays made of lithium disilicate. Only very few studies investigated wear of posterior composite crowns in vivo and reported wear to be around 40 μm/year, which is considerably lower than values found in this study [17,18]. Although there is an abundance of clinical data on the wear characteristics of direct composite restorations, literature shows a considerable variation in results from 50 to 200 μm per year [30,40,41].…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…The wear rates differed significantly between different research groups; Etman et al [38] stated wear of 148 μm after first year for lithium disilicate glass-ceramic posterior crowns, whereas Kramer et al [39] determined it as 78 μm after 4 year for ceramic inlays made of lithium disilicate. Only very few studies investigated wear of posterior composite crowns in vivo and reported wear to be around 40 μm/year, which is considerably lower than values found in this study [17,18]. Although there is an abundance of clinical data on the wear characteristics of direct composite restorations, literature shows a considerable variation in results from 50 to 200 μm per year [30,40,41].…”
Section: Discussioncontrasting
confidence: 61%
“…DeLong et.al reported that the estimation of superimposition for samples of clinical studies usually fluctuate from 10 to 20 μm per point; they considered the superimposition of less than 10 μm to be an excellent fit, whereas a value of more than 50 μm indicates a poor fit [15]. This goes in line with other clinical investigations in measuring wear, where workflow inaccuracy in the range of 15-20 μm was considered acceptable [18,[23][24][25][26]. Schmid-Schwap et al [27] even set the limit at 30 μm for standard deviation/workflow inaccuracies for molars as reasonable, as they are more difficult to superimpose.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Finally, the absence of metallic parts in the FRC structure allows their use also in patients allergic to nickel or other metals. Noteworthy is that FRCs can be indicated in patients who need to undergo nuclear magnetic resonance exams [ 78 ].…”
Section: Advantages Of the Use Of Frcsmentioning
confidence: 99%
“…Previous studies have suggested that the use of resin-veneered restorations with metallic frameworks for implant-supported prostheses eases the occlusal force or stress distribution around the implant 10,11) . However, composite resins have drawbacks, such as their low wear resistance 12) , low fracture resistance 13) , discoloration 14) , and facilitated plaque accumulation 15) . Resin-veneered restorations with zirconia frameworks have been introduced, and favorable results have been achieved with regard to the fracture resistance 16,17) and the bond strength of the veneering composite resin to zirconia frameworks 18,19) .…”
Section: Introductionmentioning
confidence: 99%